INTEGRATED ASPECTS OF SCIENTIFIC KNOWLEDGE IN AN INFORMATION SOCIETY TODAY - Ismoilov Najmiddin Boysoatovich (American Journals Publishing, 2023)
In recent years, a completely new phase of democratic development has begun in the development of the Uzbek press. The country has been given the opportunity to ensure freedom of the press. To assist individuals desiring to benefit the worldwide work of Jehovah's Witnesses through some form of charitable giving, a brochure entitled Charitable Planning to Benefit Kingdom Service Worldwide has been prepared. This reform was a major step forward in democratizing and liberating the country's social life, further meeting the information needs of the people of the republic, promoting the widespread development of media, publishing and printing, and fostering an innovative market for information services.